Enhanced production of pleuromutilin by Pleurotus mutilus and study on its molecular structure. (1st September 2017) - Sun, Shujing; Ai, Liuying; Zhang, Haiyang; Weng, Caihong; Lai, Chunfen; Liu, Li
Highlights: A novel three-stage DO strategy was proposed to enhance the pleuromutilin yield. The production intensity (12 g/L) reached the world's highest level. More substrate was converted to pleuromutilin rather than to mycelia by DO control. Pleuromutilin contains OH, CH3, CH2, CO, COOH and polycyclic hydrocarbon. The results will promote the large scale application of pleuromutilin in food. Abstract: This study aims to enhance the accumulation of pleuromutilin by Pleurotus mutilus and to analyze the molecular structure of pleuromutilin. The results showed that a novel three-stage DO control strategy (60% DO, 1-3d; 45% DO, 4-6d; 30% DO, 7-9d) was very effective for improving the pleuromutilin accumulation and the highest production reached 12 g/L, a 4-fold increase over a constant DO strategy. Furthermore, the flow behavior of fermentation broth appeared Newtonian with a maximum μ ap of 3.9 × 10 −3 Pa·s. Meanwhile the molecular formula (C22 H34 O5 ), molecular weight (378.5) and structural formula of pleuromutilin were concluded based on spectroscopy and element assay. The main components were hydroxyl, methyl, methylene, carbonyl, carboxyl, and polycyclic hydrocarbon. This work demonstrated that DO strategy was suitable for scalable production of pleuromutilin, which makes pleuromutilin more affordable as materials in food.